QUILLING : The art of paper filigree - Reid, Philippa (Ramsbury, [England] : The Crowood Press, 2019)
Quilling is a centuries-old art, which requires just three elements - your fingers, paper strips and glue. This practical guide demonstrates the techniques with step-by-step instructions and photos, and explains the best way to develop your skills and thereby push the creative boundaries of this art. Written by a passionate paper artist, it is a comprehensive guide that will inspire both novice and experienced quillers, as well as mixed media artists wishing to explore the potential of paper filigree work. Projects covered within this book include making vortex coils, pixie-hood loops, huskings, multi-strip open coils, fringed flowers, ring coil tracery patterns, folded ring coils and rolling a perfect spiral-centred coil without the need for a quilling tool. There is also advice on forming letters and abstract shapes with quilling and building 3D models from solid coils.
Includes index
Keywords: Paper quillwork